TLR2 Promotes Vascular Smooth Muscle Cell Chondrogenic Differentiation and Consequent Calcification via the Concerted Actions of Osteoprotegerin Suppression and IL-6–Mediated RANKL Induction. Issue 3 (March 2019) - Lee, Guan-Lin; Yeh, Chang-Ching; Wu, Jing-Yiing; Lin, Hui-Chen; Wang, Yi-Fu; Kuo, Ya-Yi; Hsieh, Yi-Ting; Hsu, Yu-Juei; Kuo, Cheng-Chin
Abstract : Objective—: Vascular smooth muscle cell (VSMC) transformation to an osteochondrogenic phenotype is an initial step toward arterial calcification, which is highly correlated with cardiovascular disease–related morbidity and mortality. TLR2 (Toll-like receptor 2) plays a pathogenic role in the development of vascular diseases, but its regulation in calcification of arteries and VSMCs remains unclear. We postulate that TLR2-mediated inflammation participates in mediating atherosclerotic arterial calcification and VSMC calcification. Approach and Results—: We found that ApoE −/− Tlr2 −/− genotype in mice suppressed high-fat diet–induced atherosclerotic plaques formation during initiation but progressively lost its preventative capacity, compared with ApoE −/− mice. However, TLR2 deficiency prohibited high-fat diet–induced advanced atherosclerotic calcification, chondrogenic metaplasia, and OPG (osteoprotegerin) downregulation in the calcified lesions. Incubation of VSMCs in a calcifying medium revealed that TLR2 agonists significantly increased VSMC calcification and chondrogenic differentiation. Furthermore, TLR2 deficiency suppressed TLR2 agonist–mediated VSMC chondrogenic differentiation and consequent calcification, which were triggered via the concerted actions of IL (interleukin)-6–mediated RANKL (receptor activator of nuclear factor κB ligand) induction and OPG suppression. Inhibition experiments with pharmacological inhibitors demonstrated that IL-6–mediated RANKL induction is signaled by p38 and ERK1/2 (extracellular signal-regulated kinase 1/2) pathways, whereas the OPG is suppressed via NF-κB (nuclear factor κB) dependent signaling mediated by ERK1/2. Conclusions—: We concluded that on ligand binding, TLR2 activates p38 and ERK1/2 signaling to selectively modulate the upregulation of IL-6–mediated RANKL and downregulation of OPG. These signaling pathways act in concert to induce chondrogenic transdifferentiation of VSMCs, which in turn leads to vascular calcification during the pathogenesis of atherosclerosis. Abstract : Supplemental Digital Content is available in the text.